THE INFLUENCE OF EDUCATORS ON ENHANCING CIVIC KNOWLEDGE AMONG JUNIOR HIGH SCHOOL STUDENTS IN PPKN COURSES AT CREDO KOLONGAN CHRISTIAN CHURCH - Tiagas, Gita Christina; Biringan, Julien; Wua, Telly Delly; Melo, Isye (Jambura Journal Civic Education, 2025)
This study seeks to elucidate the role of Pancasila and CitizenshipEducation (PPKn) teachers in enhancing students' civic knowledge,delineate the pedagogical strategies employed, and identify factorsinfluencing the advancement of students' understanding of civicknowledge at Kredo Kolongan Christian Junior High School. The researchis concentrated on PPKn instructional practices within the classroomsetting and the dynamics of teacher-student interactions. A qualitativedescriptive methodology with a naturalistic approach was employed. Datawere collected from PPKn teachers and students through observation, in-depth interviews, and documentation. The data analysis was conductedsystematically through the stages of data reduction, data presentation, andconclusion drawing to provide a comprehensive and in-depthunderstanding of the phenomenon under investigation. Data validity wasensured through source and technique triangulation. The findings indicatethat PPKn teachers play a pivotal role in enhancing students' civicknowledge, particularly through their roles as facilitators and moderatorsin the learning process. Teachers not only prepare and manage learningactivities but also guide interactions and discussions to be effective andstructured. The pedagogical strategies implemented include discussions,project-based learning, case studies, and role-playing, which foster activestudent participation and reinforce conceptual understanding.Furthermore, the enhancement of civic knowledge is influenced by severalsupporting factors, namely teacher competence, student learningmotivation, and the availability of adequate learning facilities andinfrastructure. These findings demonstrate that the success of PPKninstruction is significantly determined by the synergy between the role ofteachers, pedagogical strategies, and other supporting factors.